PENGARUH PEMANFAATAN ABU SEKAM PADI PADA BATA BETON RINGAN FOAM TERHADAP KUAT TEKAN, BERAT JENIS, DAN DAYA SERAP AIR SEBAGAI SUPLEMEN BAHAN AJAR MATA KULIAH TEKNOLOGI BETON (PADA MAHASISWA SEMESTER III PTB FKIP UNS) - Ari Sri Wahyuni; Chundakus Habsya; Ernawati Sri Sunarsih (Indonesian Journal Of Civil Engineering Education, 2015)
xt-stroke-width: 0px; "> The purposes of this research were to, (1) determine the viralslot influence of rice husk ash assmooth aggregate partial substitute and foam variation towards compressive strength,density, and absorption of lightweight foam concrete brick, (2) determine the percentage ofrice husk ash as smooth aggregate partial substitute and foam variation to achieve thecompressive strength which fulfilled SNI No. 03 – 0349 – 1989, (3) determine thepercentage of rice husk ash as smooth aggregate partial substitute and foam variation toachieve the density lightweight concrete which fulfilled SNI No. 03 – 0349 – 1989, (4)determine the percentage of rice husk ash as smooth aggregate partial substitute and foamvariation to achieve the absorption which fulfilled SNI No. 03 – 0349 – 1989, (5) producecourse material supplement of concrete technology on the influence of using rice husk ash inlightweight foam concrete brick toward compressive strength, density, and absorption.This research used experimental method and data analysis techniques used regressionanalysis. Variables in the study were (1) dependent variables: compressive strength, density,and absorption of lightweight foam concrete bricks, (2) independent variables: the substituteof smooth aggregate to rice husk ash with variation 0%, 25%, 35%, and 45% and foamvariation 0,2 and 0,3 of concrete volume.Based on the results of the study concluded that, (1) variation of rice husk ash andfoam was strongly influence towards the compressive strength, density, and absorption oflightweight foam concrete bricks, (2) There was no percentage of rice husk ash and foam toachieve the compressive strength of lightweight foam concrete brick which fulfilled SNI No.03 – 0349 – 1989, (3) All percentages of rice husk ash and foam variation produced thedensity value of lightweight foam concrete brick which fulfilled SNI No. 03 – 0349 – 1989, (4)All percentages of rice husk ash and foam variation produced the absorption value oflightweight foam concrete brick which fulfilled SNI No. 03 – 0349 – 1989, (5) the outputcourse materials was a course materials supplement about the influence of the use rice huskash as partly smooth agregate substitute of lightweight foam concrete brick to compressivestrength, density, and absorption.Keywords: rice husk ash, foam, lightweight foam concrete bricks.